2020
DOI: 10.3389/fimmu.2020.00768
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Levels of Mitochondrial DNA and Normal Inflammasome Gene Expression in Monocytes Characterize Patients With Septic Shock Due to Multidrug Resistant Bacteria

Abstract: Inflammation in MDR Septic Shock Conclusion: Despite many limitations, our data suggest that in patients with septic shock caused by MDR pathogens the expression of main inflammasome genes was comparable to that of healthy patients without infection. Furthermore, our data evidence a possible role of mtDNA as a prognostic marker of severity in septic shock from MDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…in addition, mtdna was positively associated with mortality in patients who were hospitalized for up to 28 days. Further studies confirmed these results (32)(33)(34)(35). Additionally, other studies have suggested that mtdna serves a key role in the pathogenesis of severe trauma, major abdominal surgery, acute lung injury (ali)/acute respiratory distress syndrome (ARDS), ischemia/reperfusion (I/R) injury, inflammatory bowel disease, rheumatoid arthritis, systemic lupus erythematosus (Sle), myocarditis and myocardial infarction (1,15,19,(36)(37)(38).…”
Section: Mtdnasupporting
confidence: 68%
“…in addition, mtdna was positively associated with mortality in patients who were hospitalized for up to 28 days. Further studies confirmed these results (32)(33)(34)(35). Additionally, other studies have suggested that mtdna serves a key role in the pathogenesis of severe trauma, major abdominal surgery, acute lung injury (ali)/acute respiratory distress syndrome (ARDS), ischemia/reperfusion (I/R) injury, inflammatory bowel disease, rheumatoid arthritis, systemic lupus erythematosus (Sle), myocarditis and myocardial infarction (1,15,19,(36)(37)(38).…”
Section: Mtdnasupporting
confidence: 68%
“…From all animal models, we demonstrated the gut translocation of bacteria-free DNA in sepsis with LPS-bacterial DNA synergy, possibly through the simultaneous TLR-4 and TLR-9 activation on macrophages [49,50]. The profound inflammation induces mitochondrial injury [76,77] and mitochondrial free DNA in systemic circulation, which further facilitate inflammatory responses [78,79] in several immune cells including macrophages [80]. Here, LPS induced M1 macrophage polarization [56], partly through the acceleration of glycolysis, the main energy source of the cells during the hyper-inflammatory stage, despite the reduction in mitochondrial activities (mitochondrial abundance, mtDNA, and maximal respiration), supporting previous publications [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are important for ATP production and mitochondrial free DNA in serum is associated with sepsis severity [ 40 , 56 , 57 ], partly on account of cGAS activation [ 58 ]. Here, impacts of mitochondria on LPS-stimulated WT macrophages were demonstrated by (i) the presence of mitochondria-associated-genes, as determined by RNA sequencing analysis, and (ii) enhanced glycolysis with decreased maximal respiration, as determined with extracellular flux analysis [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%